Estimation of Net Primary Productivity and Net Annual Assimilation in the Forests of Kumaun Himalaya - Sharma, Richa; Chaudhry, Smita; Sharma, Neeraj Kumar (Indian Forester, 2021)
Estimation of carbon uptake by the forests is required to measure the carbon flux of a region. In present study, net primary productivity (NPP) and net annual assimilation (NAA) of carbon was estimated in forests of Kumaun Himalaya by integration of field based measurements and information generated using satellite data. Aboveground NPP was estimated by quantification of aboveground biomass increment, root mortality and litterfall. Root mortality value was added to the biomass accumulation of root component to compute the total belowground productivity. Net Annual Assimilation (NAA) was computed as a difference between carbon uptake in NPP and litterfall plus root mortality. NPP values ranged from 5.20 t/ha/yr (degraded sal forest) to 21.38 t/ha/yr (temperate conifer forest). Total estimated values of net annual uptake of carbon and net annual assimilation of carbon in the study area were 748.93 Ã— 104 t/yr and 457.27 Ã— 104 t/yr, respectively. Estimation of NPP and NAA are useful for further computation of carbon flux to know the status of forest as sink or source of carbon to the atmosphere.